2000
DOI: 10.1890/0012-9658(2000)081[2799:apaocr]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

A PLURALISTIC ANALYSIS OF CHARACTER RELEASE IN PUMPKINSEED SUNFISH (LEPOMIS GIBBOSUS)

Abstract: While the importance of competition in adaptive divergence has recently been demonstrated in a number of systems, its interaction with other ecological factors has been neglected. We attempt a more pluralistic approach in this comparative study of divergence in pumpkinseed sunfish (Lepomis gibbosus) from the Adirondack region of New York. In some lakes, pumpkinseed forms that use shallow‐ and open‐water environments coexist. We tested four predictions relating to an hypothesis of character release: (1) Pumpkin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
79
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(84 citation statements)
references
References 80 publications
5
79
0
Order By: Relevance
“…Schluter & McPhail, 1992;Radtkey et al, 1997;Pfennig & Murphy, 2000;Taylor & McPhail, 2000;Grant & Grant, 2006;Rice & Pfennig, 2008), but there are few convincing cases of morphological character shifts under character release (Grant, 1972;Simberloff et al, 2000;Meiri et al, 2007Meiri et al, , 2011. This may be because a character state, in the absence of interacting species, can vary among populations owing to environmental differences (Robinson et al, 2000), and because the same character state can be equally adaptive in both sympatric and allopatric habitats. Therefore, to understand character evolution under character release, it is important to examine the effects of environmental factors other than the presence/absence of interacting species on the character state in question (Meiri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Schluter & McPhail, 1992;Radtkey et al, 1997;Pfennig & Murphy, 2000;Taylor & McPhail, 2000;Grant & Grant, 2006;Rice & Pfennig, 2008), but there are few convincing cases of morphological character shifts under character release (Grant, 1972;Simberloff et al, 2000;Meiri et al, 2007Meiri et al, , 2011. This may be because a character state, in the absence of interacting species, can vary among populations owing to environmental differences (Robinson et al, 2000), and because the same character state can be equally adaptive in both sympatric and allopatric habitats. Therefore, to understand character evolution under character release, it is important to examine the effects of environmental factors other than the presence/absence of interacting species on the character state in question (Meiri et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Although experimental studies suggest that pumpkinseed above 80 mm use Daphnia with less profitability than other prey, such as gastropods (Mittelbach 1984), some investigations conducted in North America have showed that adult pumpkinseeds can eat large quantities of zooplankon in lakes without the bluegill or other zooplanktivorous species, sometimes developing a pelagic morphotype (Robinson et al 1993(Robinson et al , 2000. The adult bluegill is morphologically better adapted than the pumpkinseed to eat zooplankton and when the two species are sympatric the former usually precludes the utilisation of zooplankton by the pumpkinseed (Osenberg et al 1988.…”
Section: Diet Of Invasive Centrarchids In the Iberian Peninsula 29mentioning
confidence: 99%
“…Its functional morphology includes specialized traits for feeding on large armored invertebrates such as snails (Lauder 1983;Wainwright et al 1991), which likely provides a competitive refuge from other sunfish (Mittelbach 1984). In the absence of bluegill sunfish (L. macrochirrus), a zooplankton generalist, some pumpkinseed sunfish are found in open water (pelagic) habitats of postglacial lakes, where they feed on zooplankton and are phenotypically divergent from local pumpkinseed sunfish that inhabit the shallow inshore littoral habitat (Robinson et al 1993;Robinson et al 2000;Gillespie and Fox 2003;Jastrebski and Robinson 2004). Phenotypic diversity within numerous lakes in New York State (USA) and the province of Ontario (Canada) is thus represented by a trophically related polyphenism bounded by sympatric littoral and pelagic ecomorphs (Robinson et al 1993;Robinson et al 2000;Gillespie and Fox 2003;Jastrebski and Robinson 2004).…”
Section: Pumpkinseed Sunfish Polyphenismmentioning
confidence: 99%
“…We created a balanced sampling design by choosing three lakes within each of four contemporary drainage systems, two drainages in each of two regions (Ontario and New York, approximately midway between glacial refugia in the Mississippi drainage, and along the Atlantic seaboard). Approximately 50 individuals from each littoral and pelagic habitat in every lake were collected using sampling techniques consistent with previous studies (Robinson et al 2000;Gillespie and Fox 2003;Jastrebski and Robinson 2004). Fish were collected by angling, or captured in fish traps (35-cm diameter × 90-cm long; 8-cm diameter aperture).…”
Section: Field Collectionsmentioning
confidence: 99%
See 1 more Smart Citation